Pengaruh Kemudahan Akses, Kepercayaan Nasabah, dan Kualitas Informasi terhadap Tingkat Loyalitas Nasabah Bank Syariah Lampung - Ilham Rizoni; Astriani, Astriani; Anggun Okta Fitri (Jurnal Bersama Ilmu Ekonomi (EKONOM), 2025)
This study aims to examine the effect of ease of access, customer trust, and information quality on the level of customer loyalty of Islamic banks. In the era of rapid digitalization, ease of access is an important factor in improving customer experience, while high trust in Islamic banks serves as the main pillar in building long-term relationships. In addition, the quality of accurate, relevant, and transparent information also plays a crucial role in providing a clear understanding of sharia-based products and services. Using a quantitative approach and survey design, data were collected through questionnaires collected from 300 respondents in member countries of the Organization of Islamic Cooperation (OIC). The results of the analysis using Structural Equation Modeling (SEM) show that ease of access, consumer trust, and information quality have a positive and significant effect on consumer loyalty. This study is expected to provide new insights for the development of Islamic bank strategies in increasing customer loyalty amidst increasingly fierce competition. These findings also have practical implications for banks